(untitled) (Research, Society and Development, 2020)
Patient safety is one of the most important approaches to patient care, directly linked to the management and quality of care. One of the problems that threatens security and prevents the achievement of more effective results in health care, refers to the constant failures in nursing care, described as Adverse Events. The objective is to report nursing care regarding patient safety in hospitals. It is an integrative review with ten articles selected in the Lilacs and SciELO databases between the period 2015 and 2020. After reading, analyzing and interpreting the data, the existence of nursing actions essential to the patient safety. It becomes relevant to provide training to nursing professionals to make them able to recognize situations of possible risk to the patient and focus on promoting safety. Thus, the research reflects on the importance of identifying and communicating an error with the records in nursing care in order to maximize the safety culture.